Case Report: Identification of the First Synonymous Variant of Myosin Binding Protein C3 (c.24A>C, p.P8P) Altering RNA Splicing in a Cardiomyopathy and Sudden Cardiac Death Case - Jin, Jie-Yuan; Xiao, Jiao; Dong, Yi; Sheng, Yue; Guo, Ya-Dong; Xiang, Rong (Frontiers in Cardiovascular Medicine, 2022)
Background Sudden cardiac death (SCD), based on sudden cardiac ejection cessation, is an unexpected death. Primary cardiomyopathies, including dilated cardiomyopathy (DCM), are one of main causes of SCD. The DCM is characterized by a cardiac dilatation and a reduced systolic function with a prevalence of 1/250 in adults. The DCM has been reported with more than 60 disease-causing genes, and MYBPC3 variants are one of the most common and well-known causes of DCM. Methods We identified a 29-year-old female who died of SCD. We performed a whole-exome sequencing (WES) to detect her genetic etiology and used minigene modeling and immunohistochemistry staining to verify the pathogenicity. Results We determined that the woman died of SCD caused by DCM due to an identified novel synonymous variant of MYBPC3 (NM_000256.3: c.24A>C, p.P8P) in the deceased. The variant can result in abnormal splicing, which was confirmed by minigene models and immunohistochemistry staining. Conclusion We may have identified the first deleterious synonymous variant of MYBPC3 in an SCD case and verified its significant impact on RNA splicing. Our description enriched the spectrum of MYBPC3 variants and emphasized the significance of synonymous variants that are always disregarded in genetic screening.